PEMBATASAN USIA PERNIKAHAN DALAM UNDANG-UNDANG NOMOR 16 TAHUN 2019 TERHADAP PRAKTIK NIKAH DIBAWAH UMUR DI KOTA BOGOR - Susman Susman; Kholil Nawawi; Syarifah Gustiawati Mukri (Universitas Pahlawan Tuanku Tambusai, 2022)
Early marriage or called underage marriage is a marriage carried out by two married couples between a man and a woman, both of whom do not meet the age requirements for holding a legally valid marriage as stipulated in Law Number 16 of 2019 Regarding Amendments to Law Number 1 of 1974 concerning Marriage. In this law, it is stated that marriage can only be allowed if both male and female have reached the age of 19 years. The approach used by the author is a case study (case study). This research method is descriptive qualitative, which means that the data obtained through observation, interviews, documentation, analysis, field notes, and then compiled directly at the research site. From the results of the study we can conclude that there was an increase in the number of underage marriages, especially in the city of Bogor, Tanah Sareal sub-district, both before and before the enactment of Law Number 16 of 2019 in October 2019. This is evidenced by the percentage of early marriage rates in the city of Bogor from year to year. In addition, based on the results of the study, there are several backgrounds that cause early marriage in the city of Bogor, including the lack of religious understanding, economic factors, lack of education, pregnancy out of wedlock (married by accident). Keywords: Marriage, Age Limit, Marriage Law